Anxiolytic effects of Dichrocephala integrifolia leaf aqueous extract on alcohol withdrawal-induced anxiety in mice: Involvement of the GABAergic pathway - Nadège Emégam Kouémou; Bertrand Yuwong Wanyu; Jacqueline Kameni Njapdounke; Simon Pale; Paul Aimé Noubissi; Rosaline Fonkem Manyi; Germain Sotoing Taiwe (Scientific African, 2024)
Ethanol withdrawal syndrome is a life-threatening state that results from a sudden termination of chronic alcohol intake. One of the manifestations of ethanol withdrawal syndrome is anxiety. Dichrocephala integrifolia is a plant used in Africa in the treatment of alcohol use disorders. This study aimed to evaluate the effects of Dichrocephala integrifolia on ethanol withdrawal anxiety in mice. Young adult Swiss mice were arranged into seven groups of six mice each. Groups II to VII received ethanol in increasing concentration for 20 days. Following ethanol withdrawal, mice were administered distilled water (Group II), Dichrocephala integrifolia (25,50,100 and 200 mg/kg) (Groups III-VI) or diazepam (Group VII). Behavioural assessments were performed using the elevated plus maze, the open field and the hole board tests. Gamma-aminobutyric acid (GABA) concentration, GABA-Transaminase and glutamic acid decarboxylase activities were assessed in the brain. In the elevated plus maze, Dichrocephala integrifolia (100 mg/kg) significantly (p < 0.01) increased the percentage of open arms entries from 20.5 ± 1.56% in the negative control, to 65.3 ± 2.46%. In the hole board, the number of head dipping raised from 27.17 ± 0.60 in the negative control to 61.33 ± 2.82 (p < 0 0.01) at the dose 200 mg/kg of Dichrocephala integrifolia. Likewise, diazepam, Dichrocephala integrifolia (200 mg/kg) significantly (p < 0.01) raised GABA concentration from 267.70 ± 5.18 µg/g of tissue in the negative control to 395 ± 5.55 µg/g of tissue. The plant extract (200 mg/kg) reduced the activity of GABA-Transaminase from 101 ± 2.60 pg/min/mg of tissue in the negative control to 42.5 ± 2.35 pg/min/mg of tissue. From these results, we can conclude that, by enhancing the GABAergic neurotransmission, Dichrocephala integrifolia has anxiolytic activities against ethanol withdrawal anxiety and can therefore be a good drug candidate for the treatment of alcohol addiction.